DRUG DISCOVERY FOR PARASITIC DISEASES AND BACTERIAL DISEASES POWERED BY TECHNOLOGY ENABLED BY PHARMACOLOGY INFORMED BY CLINICAL SCIENCE - Khulood Fahad Alabbosh; Sakina Ibrahim Ali Abonaib; Naglaa M Shalaby; Musa Elhag; Sozan M. Abdelkhalig; Hiba Mahgoub Ali Osman; Abdulmajeed Lafi Alruwaili; Fawaz Saror Alrasheedi; Amany M. Khalifa (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This work focuses on the drug development for parasitic and bacterial diseases using a combination of computational, experimental, and clinical methods for drug identification. It employs molecular docking, high through put screening (HTS), pharmacological activity and CRISPR-Cas9 assay for determining the potential therapeutic value of the tested compounds, their toxicity and demonstrating that the targets are indeed valid. In order to gain insights into the current therapy and advanced technologies in drug development, a literature search was also carried out. The authors found Compound C1 to be the most potent and selective hit that bind strongly, possesses good biological activity, low cytotoxicity and good gene target profile. The integration of different Endocrine techniques enabled the identification and prioritization of drug candidates; this study presents a sound framework upon which further clinical trials may be based. This research highlights the need to work in a team when conducting drug discovery and development using the complementary approaches that are discussed in this investigation to develop target specific drugs for parasitic and bacterial diseases.